Optimization of a precision symmetric finger-clamping garlic seed-metering device - Qian ZHANG; Yongjian WANG; Hua LI; Jifeng GAO; Yuangeng DING (Frontiers of Agricultural Science and Engineering)
This study aimed to address the sowing quality problems commonly encountered in the mechanized process of sowing garlic seeds, such as a low single-seed rate. To rectify these types of issues, the symmetric seed-collection spoons and the seed-distribution plate structures were designed based on an existing finger clip plate garlic seed-metering device. First, the optimal installation angle of the seed-distribution plate and optimal number of seed-collection spoons were determined using single-factor simulation tests based on discrete element method-multibody dynamics (DEM-MBD) coupling, and the effects of different seed-collection spoon tapers, finger clip gradual closing angles, and seed tray rotation speeds on the performance of the seed-metering device were analyzed. Second, based on the single-factor simulation tests, a quadratic regression orthogonal rotary combination simulation test was conducted using the taper of the seed-collection spoon, finger clip gradual closing angle, and seed tray rotation speed as the test factors and the single-seed rate (1 seed per spoon), empty rate (0 seed per spoon), and multiple-seed rate (≥ 2 seeds per spoon) as the test indices. Parameter optimization was performed using an established regression model. Finally, bench tests were conducted to verify the reliability of the simulation results. The results showed that the optimal parameter combinations were a seed-collection spoon taper of 1.6, a finger clip gradual closing angle of 21.4°, and a seed tray rotation speed of 31.5 r·min−1. Also, the seed-metering device exhibited a single-seed rate of 94.2%, an empty rate of 2.1%, and a multiple-seed rate of 3.7%.